Taking Multiple Exposure Into Account Can Improve Assessment of Chemical Risks. - Clerc, Frédéric; Hyacinthe Bertrand, Nicolas Jean; Rocca, Bénédicte La (Annals of Work Exposures & Health, 2018)
During work, operators may be exposed to several chemicals simultaneously. Most exposure assessment approaches only determine exposure levels for each substance individually. However, such individual-substance approaches may not correctly estimate the toxicity of 'cocktails' of chemicals, as the toxicity of a cocktail may differ from the toxicity of substances on their own. This study presents an approach that can better take into account multiple exposure when assessing chemical risks. Almost 30 000 work situations, monitored between 2005 and 2014 and recorded in two French databases, were analysed using MiXie software. The algorithms employed in MiXie can identify toxicological classes associated with several substances, based on the additivity of the selected effects of each substance. The results of our retrospective analysis show that MiXie was able to identify almost 20% more potentially hazardous situations than identified using a single-substance approach. It therefore appears essential to review the ways in which multiple exposure is taken into account during risk assessment.